2021
DOI: 10.1177/1938640020987775
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following the Use of Subtalar Arthroereisis in the Correction of Adult Acquired Flatfoot: A Systematic Review

Abstract: Background Adult acquired flatfoot deformity (AAFD) is a condition affecting approximately 3% of the adult population. It can lead to severe morbidity, and therefore, prompt treatment is of the upmost importance in maintaining and restoring function. Recently, the use of subtalar arthroereisis has become more widespread in the treatment of AAFD. The purpose of this systematic review is to examine the clinical and radiological outcomes of AAFD when treated with subtalar arthroereisis. Methods Studies involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, two systematic reviews and one meta-analysis were previously published. Baryeh et al [ 36 ] reported partially conclusive data supporting the subtalar AR as an adjunct treatment, but the analysis was limited to adult acquired flatfoot. Suh et al [ 34 ] performed a comparison between AR and the LCL procedures and concluded that LCL achieved more radiographic corrections and more improvements in the AOFAS score than the AR.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, two systematic reviews and one meta-analysis were previously published. Baryeh et al [ 36 ] reported partially conclusive data supporting the subtalar AR as an adjunct treatment, but the analysis was limited to adult acquired flatfoot. Suh et al [ 34 ] performed a comparison between AR and the LCL procedures and concluded that LCL achieved more radiographic corrections and more improvements in the AOFAS score than the AR.…”
Section: Discussionmentioning
confidence: 99%